Intra-abdominal mass with empty scrotum in adult male - Parajuli, Purushottam (Urol Case Rep, 2020)
Cryptorchidism is one of the most common congenital anomaly affecting new born males. Early identification and management at 6–12 months is recommended. Occasionally adult male can present for the first time with intra-abdominal mass with empty ipsilateral scrotum. These tumors may present at advanced stage and management may be challenging at times.